Multiplicity dependence of light (anti-)nuclei production in p-Pb collisions at sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physics letters, 2020)
The measurement of the deuteron and anti-deuteron production in the rapidity range −1<y<0 as a function of transverse momentum and event multiplicity in p-Pb collisions at sNN = 5.02 TeV is presented. (Anti-)deuterons are identified via their specific energy loss dE/dx and via their time-of-flight. Their production in p-Pb collisions is compared to pp and Pb-Pb collisions and is discussed within the context of thermal and coalescence models. The ratio of integrated yields of deuterons to protons (d/p) shows a significant increase as a function of the charged-particle multiplicity of the event starting from values similar to those observed in pp collisions at low multiplicities and approaching those observed in Pb-Pb collisions at high multiplicities. The mean transverse particle momenta are extracted from the deuteron spectra and the values are similar to those obtained for p and Λ particles. Thus, deuteron spectra do not follow mass ordering. This behaviour is in contrast to the trend observed for non-composite particles in p-Pb collisions. In addition, the production of the rare He3 and He‾3 nuclei has been studied. The spectrum corresponding to all non-single diffractive p-Pb collisions is obtained in the rapidity window −1<y<0 and the pT-integrated yield dN/dy is extracted. It is found that the yields of protons, deuterons, and He3, normalised by the spin degeneracy factor, follow an exponential decrease with mass number.